Bay Leaves (Syzygium polyanthum) and Rosella Flowers (Hibiscus sabdariffa) are Effective In Reducing Blood Pressure - Ariyanto Nugroho; Siti Fadlilah; Adi Sucipto; Eko Mindarsih (Universitas Aisyah Pringsewu, 2022)
The effort to treat hypertension is blood pressure management. Some plants that can treat blood pressure are bay leaves and rosella flowers. The aim is to determine the effects of bay leaves and rosella flowers on blood pressure in people with hypertension. The research used an experimental approach with a pretest and posttest control group design. The control group sample was 18 people, the bay leaves group was 17, and the rosella group was 17. The subject was taken using simple random sampling. Instruments to measure blood pressure were Sphygmomanometer digital and observation sheet. The statistical test used the Paired T-Test and Independent T-Test. The analysis of pretest-posttest SBP among control, bay leaves, and rosella groups were p=0.038, p=0.000, and p=0.000. The pre-posttest DBP analysis among control, bay leaves, and rosella groups were p=0.000, p=0.000, and p=0.000. The SBP and DBP between bay leaves and rosella were p=0.280 and p=0.396. The highest decrease in mean pre-posttest SBP and DBP rosellas were -12.64 and -11,41 mmHg. Bay leaves and rosella flowers effectively reduce blood pressure in people with hypertension. Rosella is more effective at lowering blood pressure in terms of the average decrease in blood pressure. As a community nurse, you can improve health promotion about complementary therapies using herbal plants such as rosella and bay leaves as an alternative therapy to maintain blood pressure in hypertensive patients. Abstrak: Upaya pengobatan hipertensi adalah mengelola tekanan darah. Beberapa tanaman yang dapat digunakan untuk mengelola tekanan darah adalah daun salam dan bunga rosella. Tujuan penelitian untuk mengetahui pengaruh daun salam dan bunga rosella terhadap tekanan darah pada penderita hipertensi. Penelitian menggunakan pendekatan eksperimen dengan desain pretest and posttest control group design. Sampel kelompok kontrol 18 orang, kelompok daun salam 17 orang, dan kelompok rosella 17 orang. Pengambilan sampel dilakukan secara simple random sampling. Alat untuk mengukur tekanan darah adalah Sphygmomanometer digital dan lembar observasi. Uji statistik menggunakan Paired T-Test dan Independent T-Test. Analisis pretest-posttest SBP antara kelompok kontrol, daun salam, dan rosella adalah p=0,038, p=0,000, dan p=0,000. Analisis DBP pre-posttest antara kelompok kontrol, daun salam, dan rosella adalah p=0,000, p=0,000, dan p=0,000. SBP dan DBP antara daun salam dan rosella adalah p=0,280 dan p=0,396. Penurunan rerata pre-posttest SBP dan DBP rosella tertinggi adalah -12,64 dan -11,41 mmHg. Daun salam, dan bunga rosella efektif menurunkan tekanan darah pada penderita hipertensi. Rosella lebih efektif dalam menurunkan tekanan darah dalam hal penurunan rata-rata tekanan darah. Sebagai perawat komunitas dapat meningkatkan promosi kesehatan tentang terapi komplementer dengan menggunakan tanaman herbal seperti rosella dan daun salam sebagai terapi alternatif untuk menjaga tekanan darah pada pasien hipertensi.